2020
DOI: 10.4102/phcfm.v12i1.2323
|View full text |Cite
|
Sign up to set email alerts
|

Different models of pharmaceutical services and care in primary healthcare clinics in the Eastern Cape, South Africa: Challenges and opportunities for pharmacy practice

Abstract: Background: Primary health care (PHC) re-engineering forms a crucial part of South Africa’s National Health Insurance (NHI), with pharmaceutical services and care being crucial to treatment outcomes. However, owing to a shortage of pharmacists within PHC clinics, task-shifting of the dispensing process to pharmacist’s assistants and nurses is common practice. The implications of this task-shifting process on the provision of pharmaceutical services and care remains largely unstudied.Aim: The study aimed to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“… 47 Most KPIs were developed for clinical services. For years, the pharmacy profession was focused simply on the supply of medicines rather than pharmaceutical care-related roles 48 and the findings highlight the increasing role of pharmacists in direct patient care. However, this finding reflects a gap in the availability of studies that developed indicators for other pharmaceutical services, such as the supply of medicines and drug dispensing.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Most KPIs were developed for clinical services. For years, the pharmacy profession was focused simply on the supply of medicines rather than pharmaceutical care-related roles 48 and the findings highlight the increasing role of pharmacists in direct patient care. However, this finding reflects a gap in the availability of studies that developed indicators for other pharmaceutical services, such as the supply of medicines and drug dispensing.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy Education 21(1) 203 -215 212 pharmacist nor offer services from a formal pharmacy (Bobbins et al, 2020). It is the hope of the School that the development and expansion of this programme may add to the normalisation of the presence of pharmacists in public primary health care clinics beyond the pharmacy in a patient-centred role (as opposed to a product centred one) that overlaps and compliments that of the nurse in primary health care.…”
Section: Implementation Of Tuberculosis Screening In South Africamentioning
confidence: 99%
“…Nurses are unable to cope with the additional function of medicine supply management because of the increased workload. In a study conducted in one province in South Africa, nurses reported a high workload at primary healthcare clinics where dispensing services had to be incorporated into an already time-constrained patient consultation schedule (Bobbins, Burton & Fogarty 2020 ).…”
Section: Introductionmentioning
confidence: 99%